2018
DOI: 10.1111/echo.14145
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on cardiac electromechanical function in asymptomatic individuals

Abstract: Background and Aim Whether aging affects left ventricular (LV) filling and ejection and the LV electric function is not well established. We investigated the effect of normal aging on echocardiographic measurements of LV morphology and function, LV electric function and the relationship between LV electric and mechanical function in asymptomatic individuals. Methods As part of a cross‐sectional survey for the prevalence of coronary risk factors in the general population in Caltanissetta, Italy, individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Notably, there was no significant correlation between absolute LVFT and QRS duration or between absolute LVFT and LVEF. Vancheri et al did not find a significant correlation between the QRS duration and LVFT 26 . However, Charisopoulou and colleagues found that LVFT was positively correlated with stroke volume 27 .…”
Section: Discussionmentioning
confidence: 87%
“…Notably, there was no significant correlation between absolute LVFT and QRS duration or between absolute LVFT and LVEF. Vancheri et al did not find a significant correlation between the QRS duration and LVFT 26 . However, Charisopoulou and colleagues found that LVFT was positively correlated with stroke volume 27 .…”
Section: Discussionmentioning
confidence: 87%
“…The LV mechanical behavior during pre-ejection and post-ejection is a complex and controversial topic [ 8 10 ]. Pre-ejection is traditionally biphasic [ 11 ], the first phase is referred to as electromechanical delay (EMD) and is represented by the interval from the onset of the electrocardiographic QRS complex to mitral valve closure (MVC), and the second phase is referred to as isovolumic contraction (IC) which follows MVC and is characterized by a rapid increase in LV pressure before opening of the aortic valve.…”
Section: Discussionmentioning
confidence: 99%